TONDA FISHING BOAT REPAIR IN SHIPYARD PASIA TIKU DISTRICT TANJUNG MUTIARA PORT AGAM REGENCY WEST SUMATERA PROVINCE - Ulya Ulfi Rahmi; Syaifuddin '; Ronald M Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in April 2013 at the Shipyard that runs Tiku Tanjung MutiaraAgam District of West Sumatra Province. This study uses a survey method that aims to determinethe cause of the damage and engineering maintenance / repair on Trolling Fishing boats inDockyard that runs Tiku.The results showed that the damage to the vessel's fishing trolling in Dockyard that runsTiku caused by vermin, the effects of temperature and weather. Repair techniques performed inGalngan ship that runs Tiku is simple and traditional, which is still based on the expertise andexperience of the workers ship. Ship materials used in shipyards that runs Tiku is wood and zinc.To care used wooden boats are wooden keruing (Dipterocarpus spp), wood laban (Vitexpubesceus), wood resak (Vatica spp), and red meranti (Shore spp).Keywords: Biro Klasifikasi Indonesia (BKI), wooden ship repair,